Political of School Pemberdayaan Masyarakat Warmon Kokoda dalam Menciptakan Kampung Sadar Politik - Muchammad Farid (Jurnal Abdimasa Pengabdian Masyarakat, 2022)
Abstract In West Papua, in Sorong Regency, especially in the Mayamuk Mabusun Settlement Unit III (SP3), the Muslim community of Warmon Kokoda resides, which has a high level of active participation in the absorption of voting rights. The absorption of voting rights is not accompanied by implementation and concrete evidence from politics in proving the realization of his campaign promises. Politicians only use the voice of the community when needed. This is because there is no political awareness from the Muslim community of Warmon Kokoda which focuses on practical politics and money politics. To anticipate this, the community service program organized by the Muhammadiyah Education University of Sorong, West Papua (Unimuda Sorong) with the Muslim Community Strategy partner Warmon Kokoda settlement unit III (SP3) Mayamuk Mabusun carried out a community service program. to minimize the level of practical politics, money politics, and provide a level of awareness regarding the importance of clean politics. The community empowerment program consists of programs, namely preventive programs regarding the dangers of dirty politics, advocating for choosing the one who is trustworthy and being more selective in choosing the government. The implementation of the Community Service Program is divided into several stages, namely the first stage in the form of a debriefing and education program, the second stage is a program counseling for the Warmon Kokoda community and the third stage is a political-related simulation stage. In general, the implementation of this political school program runs systematically and gets the attention of Fishum Unimuda Sorong, making it easier for servants to run the program. The urgency of this program is to make the public critically aware of politics, smart in choosing, in politics and rejecting all forms of dirty politics. Keywords: Political Awareness School, Warmon Kokoda Muslim Community, Community Empowerment